EFL teachers’ practices while teaching reading comprehension in Jordan: Teacher development implications - Naima Al-husban (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2019)
This study investigated in-service English as foreign language (EFL) teachers’ practices while teaching reading comprehension at schools. Thirty EFL teachers were observed to identify their current practices and teaching quality. To triangulate the trustworthiness of the data, out of those thirty, ten EFL teachers were interviewed. The observation data were analyzed using descriptive statistic particularly frequencies and percent, and the interview data were analyzed using thematic content analysis. The findings of the study revealed that teachers taught students reading comprehension traditionally. Most of the observed and interviewed teachers knew the names of the reading comprehension strategies and the stages of teaching reading comprehension. However, they did not know how to employ and practice them. Based on the results, it is necessary to design professional development programs to empower EFL teachers on how to present these strategies and to conduct further research on this topic while considering other variables, like experience and the nature of curricula.